The Impact of Associative Game toward Social Interaction in ChildrenChildhood is the playing period which is expected to support matureness in growth and development; when that time not used as well as possible surely will eventually disturb the growth su - Pratiwi, Tiara Fatma; Nurjanah, Siti; Maisaroh, Siti; Wahdi, Achmad; Puspitosari, Dewi Retno (International Journal of Psychosocial Rehabilitation, 2020)
Childhood is the playing period which is expected to support matureness in growth and development; when that time not used as well as possible surely will eventually disturb the growth such as child social interaction. It can be weak with only quiet as in the class, difficult sociable and children unruly. The purpose of this research is to discover the influence of associative game toward the increased of social interaction in children at RA Baitul Karim Surabaya. The design of the research is pre experiment with a kind of one group pretest-posttest design, use probability of sampling; a simple random sampling. The data collection use sheets of observation data and analyzed by Wilcoxon. The result of the research showed that pre-test had less social interaction and post-test had more social interaction, the value received, so Ho was rejected means there was an influence of the associatie game toward the child social interaction. The conclusions of this research were that more and more often associative game applied; it can increase the child social interaction. The suggestion to nursing profession is, associative game could be one of the cares of nursing in developing child social interaction.